Supervision as a factor of social work improvement - Кривоконь, Наталія Іванівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
The necessity of wider introduction of supervision as a special form of practical professional activities support of psychologists and social workers in Ukraine is shown in the article. There is presented the author’s concept and supervision practical model in psychosocial work. It covers private experience of group and individual supervision for employees of the Children’s program in the Kharkiv regional charity Jewish Fund «Hesed Shaare Tikva». The possibilities of increasing the effectiveness of specialists in psychosocial work through supervision practice are presented.